Ocular Decompression Retinopathy Following Canaloplasty for Primary Open Angle Glaucoma: A Case Report. Issue 9 (March 2016) - Li, Gai-yun; Alantaree, Samer; Wang, Jun-ming; Zhang, Hong
Abstract : Abstract: Ocular decompression retinopathy (ODR), a rare postoperative complication following glaucoma surgery, is characterized by the transient appearance of scattered retinal hemorrhages. Here, we present a unique case of ODR in a patient with primary open angle glaucoma who underwent canaloplasty. A 31-year-old male patient presented with an intraocular pressure (IOP) of 60 mm Hg in the right eye. The IOP remained over 40 mm Hg, even when treated with maximum tolerated antiglaucoma medication. Canaloplasty drastically lowered IOP in the right eye from 40 to 7 mm Hg. However, fundus examination revealed ODR after surgery. The patient was treated with tobramycin and dexamethasone. Three months after canaloplasty, IOP remained in control at 16 mm Hg and all retinal hemorrhages had completely resolved. This case demonstrates that ODR can occur following canaloplasty and physicians should be aware of this potential complication in patients with severely elevated IOP. Sufficiently lowering IOP before surgery and gradually decreasing IOP during surgery may prevent ODR from occurring.